The use of different types of natural coarse aggregates in SCC design - Tobes, Juan Manuel (2010)
The shape and texture of coarse aggregate affect the properties of fresh and hardened concrete. However, there is limited information about the effects of aggregate characteristics on self-compactability, which can be relevant in countries like Argentina, where a large variety of aggregates is available even in the same region. This paper analyzes the effect of shape and texture of coarse aggregate on self-compacting concrete (SCC) properties. Four different types of coarse aggregate were selected: granitic crushed stone, quartzitic crushed stone, basaltic crushed stone and siliceous river gravel. The granitic and basaltic crushed stone presents irregular shape, rough texture and low absorption. The quartzitic crushed stone also has irregular shape and rough texture, but it has high water absorption. Finally, the natural siliceous river gravel is composed by strong particles with smooth surface and low porosity. Slump-flow, V-funnel and J-Ring tests were carried out in order to evaluate SCC properties. The influence of the mixing volume was also studied. The homogeneity of the coarse aggregate distribution was evaluated along vertical cuts on 1 m in height tubes and along a U-tube with 1.80 m height, measuring the ultrasonic pulse velocity and the unit weight in different sections. In addition, the compressive strength and modulus of elasticity were determined. From the results, was concluded that, as expected, the shape and texture of coarse aggregate modify the flowability, but also the mixing energy can strongly affect the viscosity of SCC.